If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 = 7 + -4x Reorder the terms: -7 + 3x = 7 + -4x Solving -7 + 3x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -7 + 3x + 4x = 7 + -4x + 4x Combine like terms: 3x + 4x = 7x -7 + 7x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 -7 + 7x = 7 + 0 -7 + 7x = 7 Add '7' to each side of the equation. -7 + 7 + 7x = 7 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 7 + 7 7x = 7 + 7 Combine like terms: 7 + 7 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 3x+4x+5x-2x=4x+5x+20 | | 9x-7=8x-1 | | 2x^3+9x^2+4x+6=0 | | 4x-3y+5x-2y= | | 2x^3-9x^2+4x+6=0 | | 8*10+10y=80 | | =2(3b+5)+4(2b-3) | | 4x^2+5k=(5k+1)x | | 13x-49=7x+29 | | =3(a+2b)-3b | | 2+cosx=0 | | 2+2cosx=0 | | x^2=18y^2-y^4 | | 8ab+12ab-12a= | | 7(h+1)=3+7h | | 3(g-1)=-2(2+g) | | 36x^2y^3+xy^2= | | =b(b+3)-2 | | =6(a+3)+2 | | =8a+2(5-b)-2a | | 6x^3+4x^2-14x+4=0 | | 125r^2-45= | | 3(2d+3)=12 | | 12r^2-75= | | =13a-b+3-6a+b | | 18.50+d=26.5 | | =7+a(3+b)-2 | | (49x^2-14x+1)(49x^2-15x+1)=0 | | =3+6(8+b)+2(b+b) | | =3a-4+2b-a+11 | | 15x^2+2xy-8y^2= | | 8.5+1m= |